Simulation model for determining the rational dimensions of the irreducible reserve of locomotives at the stations of its turnover - E. A. Sotnikov; M. M. Gonik; S. V. Khomyakov; S. V. Mikhaylov (Вестник Научно-исследовательского института железнодорожного транспорта, 2018)
With the introduction of polygon site technologies, the extension of locomotive circulation areas has increased the complexity of solving the problems of regulating the fleet of locomotives. Determination of the required rational size of the irreducible reserve of locomotives at the stations of its turnover is currently carried out in order to extinguish the influence on the export of the inaccuracies in the planning and inadequate depth of the forecast of the car traffic flows. Substantially this determination is made on the basis of expert assessments and does not have sufficient methodological justification. In order to exclude the loss of the traffic threads in the schedule, it is necessary to create a rational irreducible reserve of locomotives at the stations of its turnover. To solve this problem, a mathematical model of train operation has been developed on locomotive circulation areas, taking into account the daily fluctuations of train traffic, possible deviations in predicting composition formation and other factors. Performing mass calculations for various conditions will allow determining the rational size of the irreducible reserve of locomotives at the stations of its turnover and eliminate the losses associated with the cancellation of the schedule threads due to the lack of provision of finished trains by locomotives. Extensive full-scaled tests were made to determine the difference between actual and planned train traffic, which allowed determining regularities in the formation of planned values of train traffic for use in the simulation model. An algorithm for constructing a simulation model has been developed that provides for the amount of a irreducible reserve of locomotives for different conditions: changing values of the average daily train traffic in the even and odd directions of traffic, traffic incompatibility, the degree of uneven daily traffic, errors in planning (planning quality), etc. The software of the simulation model was developed and its debugging was made to perform mass calculations. The study of the problem of determining the rational size of the irreducible reserve of locomotives at the stations of its turnover was carried out with the support of the Russian Railways and the Russian Foundation for Basic Research. Project No. 17-20-01136.